The Influence of Organizational Support and Interpersonal Communication on the Quality of Public Services Through Nurses' Work Commitment at KH. Daud Arif Kuala Tungkal Regional General Hospital, West Tanjung Jabung Regency - Melia, Dessy; Zahari, M.; Rozi Yamali, Fakhrul (DINASTI RESEARCH, 2025)
This study aims to describe organizational support, interpersonal communication, nurses' work commitment, and the quality of public services at KH. Daud Arif Kuala Tungkal Regional General Hospital, West Tanjung Jabung Regency, and to analyze the influence of organizational support and interpersonal communication through work commitment on the quality of public services. The population of this study was the community or patients totaling 24,405, while the sample size in this study used Slovin's theory with a margin of error of 10% so that 100 people were obtained. This study used a quantitative approach with a survey method and used Partial Least Square (PLS) data analysis. The results showed that organizational support and interpersonal communication have an influence on the quality of nurses' services, both directly and indirectly through work commitment. This explains that when nurses feel supported by the organization, and open and effective communication between colleagues and with leaders creates a conducive and collaborative work atmosphere, then this factor can directly improve the quality of services provided to patients. Meanwhile, indirectly, organizational support and interpersonal communication can strengthen nurses' work commitment, which is demonstrated through their loyalty, responsibility, and dedication in carrying out their duties, thus having a positive impact on improving the quality of health services.